How to get things moving in EU-Western Balkan relations - Hubert Gabrisch (The Vienna Institute for International Economic Studies (wiiw), 2023)
The EU's enlargement policy with regard to the Western Balkan countries is in tension with the necessary internal reforms. Therefore, the promise of admission contrasts with the slow realisation of this promise. The dilemma results less from the Western Balkan countries' readiness for accession than from the admission capacity of the Union itself. Against this background, a further evolution of the association agreements - for example, in the direction of a customs union and 'decision-shaping' - could buy the Union time to carry through its own reforms. The legal regulations contained in other association agreements - such as the Europe Agreements and agreements with countries of the European Free Trade Area as members of the European Economic Area - offer some templates.
Keywords: F53; F55; K33; 330; Western Balkans; EU accession; association; legal basis; EU reform